1972
DOI: 10.1111/j.1528-1157.1972.tb05167.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Diphenylhydantoin and Phenobarbital on Intestinal Calcium Transport in the Rat*

Abstract: SUMMARY In vitamin D deficient rats the influence of diphenylhydantoin (DPH) and phénobarbital (PB) pretreatment on intestinal uptake of 45calcium and on the activity of CaBP was studied. The DPH rats show in contrast to the PB and control rats a significantly reduced intestinal uptake of 45calcium. However, the activity of CaBP was similar in all investigated groups. These results suggest a possibly special effect of DPH on the development of the calcium and bone disorders that have been observed in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
7

Year Published

1976
1976
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(46 citation statements)
references
References 19 publications
1
38
0
7
Order By: Relevance
“…In the present study however, the reduction found was 0.3mg/dl, which is the lower limit of this variation and was not enough to increase the PTH serum levels and was not associated with the metabolism of vitamin D. This reduction in the calcium serum levels could be attributed to the direct action of the anticonvulsants in the cells (intestine and bone) as shown in the case of phenobarbital and phenytoin but this has not yet been proven. However, in the case of carbamazepine, this asumption was in agreement with normal levels of serum 25-hydroxycholecalciferol that were found 3,10,11 . The mean total alkaline phosphatase serum levels were significantly higher in the patients than in the control group.…”
Section: Discussionsupporting
confidence: 66%
“…In the present study however, the reduction found was 0.3mg/dl, which is the lower limit of this variation and was not enough to increase the PTH serum levels and was not associated with the metabolism of vitamin D. This reduction in the calcium serum levels could be attributed to the direct action of the anticonvulsants in the cells (intestine and bone) as shown in the case of phenobarbital and phenytoin but this has not yet been proven. However, in the case of carbamazepine, this asumption was in agreement with normal levels of serum 25-hydroxycholecalciferol that were found 3,10,11 . The mean total alkaline phosphatase serum levels were significantly higher in the patients than in the control group.…”
Section: Discussionsupporting
confidence: 66%
“…With regard to calcium metabolism, clinical studies have shown that the use of antiepileptic agents was frequently associated with the development of hypocalcemia, and there is a finding that antiepileptic agents decrease intestinal transport of calcium (8,9). However, the hypocalcemia which usually leads to bone fracture was not observed when the treatment with zonisamide at 80 mg / kg for 5 weeks significantly decreased the BMD in tibial bones measured in this experiment.…”
Section: Discussionmentioning
confidence: 60%
“…Because there is evidence that transmembrane movement of sodium ion plays an important role in the cellular transport of calcium ion in both intestine and bone (33)(34)(35), it could well be that DPH inhibition of membrane permeability to sodium reduces transmembrane calcium transport in these tissues as well. In support of this view, DPH has been shown to directly inhibit intestinal calcium transport in vivo under conditions in which vitamin D metabolism is apparently not altered (12). Thus, the effect of DPH on PTH-induced cAMP generation could well occur via inhibitory effects on PTH-induced changes in intracellular calcium ion concentration.…”
Section: Effects Of Diphenylhydantoin and Phenobarbital On Bone Resormentioning
confidence: 63%
“…In addition, there is experimental evidence which suggests that anticonvulsant drugs may indeed have direct effects on mineral metabolism. Koch et al (12) have reported that DPH appears to directly inhibit intestinal calcium transport in the rat and Harris et al (9) have demonstrated that DPH can inhibit parathyroid extract-induced 45Ca release from mouse calvaria in vitro.…”
Section: Introductionmentioning
confidence: 99%